Study and practical investigations of Nano Supercapacitors. (2020) - Mani Kota Rajasekhar, Tumula; Sai Sushanth, Vellampalli; Sumathi, M.
Abstract: Capacitors are basically defined as a two-terminal electric component which stores potential energy in an electric field. The effect of the capacitor is known as capacitance. Generally, there exists some capacitance exists between any two electrical conductors in proximity in a circuit, a capacitor is a component designed to add capacitance. The capacitor was originally known as a condenser. The physical form and construction of the practical capacitors vary widely. Most capacitors contain two electrical conductors often in the form of metallic plates or surfaces separated by a dielectric medium. A conductor is generally a foil, thin film, sintered bead of metal, or an electrolyte. The nonconducting dielectric acts in order to increase the capacitor's charge capacity. Materials commonly used as the dielectrics include glass, ceramic, paper, plastic film, mica, and oxide layers. In the common world Capacitors are widely used as parts of electrical circuits in many common electrical devices. Unlike normal a resistor, an ideal capacitor does not dissipate energy. But the energy density of the capacitor is very low due to this greater number of capacitors are required to maintain a particular circuit.so to rectify these kinds of problems, we need a device which is more capable to hold the potential energy